Love and Belonging Needs in John Green’s The Fault in Our Stars - Alvin Dwi Permana; Mamik Tri Wedawati; Muhammad Dhika Arif Rizqan (Udayana Journal of Social Sciences and Humanities, 2021)
The anxiety of being treated differently unlike others is one of the myriad uncomfortable feelings which may be understood by cancer sufferer. The present study aimed to expose the needs of two cancer sufferers who loved each other. They are the main characters of the Fault in Our Stars namely Hazel and Augustus. Therefore, the researchers addressed two questions: How are the love and belonging needs of Hazel and Augustus portrayed in John Green's The Fault in Our Stars? And what are the impacts of fulfilling love and belonging needs toward Hazel and Augustus as it is portrayed in John Green’s novel The Fault in Our Stars? This study applied a qualitative approach namely content analysis. The data were analyzed and interpreted by using the hierarchy of needs which focused on love and belonging needs. The result exposed that Hazel and Augustus yearn for fulfilling their love and belonging needs instead of the other needs such as physiology, safety, self-esteem, and self-actualization. It affected significantly to their life which changed them to be more optimistic.